Armenian Manuscripts of St. Athanasius of Alexandria - Casey, Robert Pierce (Harvard theological review, 1931)
The Armenian version of the works of Athanasius is known to European scholars from four sources: (1) the list in Karekin's catalogue of early Armenian translations, (2) Conybeare's edition of the pseudo-athanasian “Dialogue between Athanasius and Zacchaeus,” (3) an article by the same scholar, ‘On the Sources of the Text of St. Athanasius,’ with accompanying collations of the Armenian of De Incarnatione et contra Arianos and Qvod unus sit Christus, and (4) the Venice edition of Armenian Athanasiana made by E. Tajezi and published with Conybeare's help at the Mechitarist press in 1899. This edition contains all the material then available in the Mechitarists' library at Venice but is not based on a complete survey of the sources. Furthermore, the manuscripts employed are (with the one exception of Cod. Venet. 818) collections of various patristic writings, and do not contain corpora of Athanasius's works such as are commonly found in Greek.